Changing Gender Relation in Medieval and Early Modern Iceland: The Role of Canon Law According to Court Case Narratives - Arnórsdóttir, Agnes S. (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
The marriage legislation of medieval Iceland are to be found in the provincial law collection of Grágás, from the late 12th and early 13th century, the New Christian Law of 1275, the royal lawbook of Jónsbók from 1281, as well as the correction of the royal law in the 14th century, and many Church statutes of the same century. These regulation, as well as the change in the legislation after the Reformation in the 16th century, can give valuable indi-cation of change in gender relation. All these regulation where highly influenced directly or indirectly by the international Church law, called canon law. In this paper I shall not primarily discuss this legal regulations rather give some ideas of how the law was used (and shaped on a textual level) at the local courts. Examples will be taken from several court case narrations.